2011
DOI: 10.1186/1743-422x-8-254
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and molecular epidemiological characteristics of acute and fulminant viral hepatitis A

Abstract: BackgroundHepatitis A virus is an infection of liver; it is hyperendemic in vast areas of the world including India. In most cases it causes an acute self limited illness but rarely fulminant. There is growing concern about change in pattern from asymptomatic childhood infection to an increased incidence of symptomatic disease in the adult population.ObjectiveIn-depth analysis of immunological, viral quantification and genotype of acute and fulminant hepatitis A virus.MethodsSerum samples obtained from 1009 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…For HAV RNA-negative cases, the mean delay between onset of symptoms and sampling was 25.5 days (range, 5-47 days), whereas for HAV RNA-positive cases, this delay was significantly lower, with a mean of 10.2 days (range, 1-49 days, p < 0.001). These findings suggest, as previously described, that the positivity of HAV RNA is correlated to the sampling time [11][12][13]. This result can be explained by the short duration of viremia, during natural history of HAV infection.…”
Section: Molecular Epidemiology Of Hepatitis a Virus Infectionsupporting
confidence: 86%
“…For HAV RNA-negative cases, the mean delay between onset of symptoms and sampling was 25.5 days (range, 5-47 days), whereas for HAV RNA-positive cases, this delay was significantly lower, with a mean of 10.2 days (range, 1-49 days, p < 0.001). These findings suggest, as previously described, that the positivity of HAV RNA is correlated to the sampling time [11][12][13]. This result can be explained by the short duration of viremia, during natural history of HAV infection.…”
Section: Molecular Epidemiology Of Hepatitis a Virus Infectionsupporting
confidence: 86%
“…HAV genotype IIIA has been reported as an aetiological agent of various other water borne outbreaks from northern 8 , southern 10 and western 11 India. Hussain et al 28 have reported genotype III as the predominant genotype (70%) followed by genotype IA (30%) in Delhi. Co-circulation and co-infections with subgenotypes IIIA and IB have been reported from Pune, western India 13 .…”
Section: Discussionmentioning
confidence: 98%
“…Hepatitis A virus is one of the most common causative agents for acute hepatitis worldwide, which accounts for approximately one quarter of clinical hepatitis cases (Yotsuyanagi et al, 1996;Kwon et al, 2000;Hussain et al, 2011). Seroprevalence of anti-HAV is highly correlated with socioeconomic status and access to clean water and sanitation (Jacobsen and Koopman, 2004).…”
Section: Discussionmentioning
confidence: 99%